THEORETICAL FRAMEWORK ON THE ROLE OF SATISFACTION IN DEVELOPING LEADERSHIP CAPACITY FOR SUCCESSFUL ORGANIZATIONAL OUTCOMES - Hakim, Adi Lukman; Fahmie, Shah Iskandar (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Employees are tools for achieving company goals. Therefore, they must be able to see, monitor and understand the existing conditions by supervisor called leader. Therefore, human resource management is important to improve their performance to achieve goals, but the reality shows that their efforts are far from what is expected in statistical department. As an example, for statistical department, one of the factors that can cause a decline in data processing is a decline in employee performance due to the level of difficulty of the data that must be managed and system updates that can hinder data processing. Additionally, there are various factors that hinder data management, such as some employees who are irresponsible in their work and have not completed their tasks according to the set targets. Other factors that can support performance include solutions that can be implemented by the organization or employees themselves, such as effective leadership in accordance with organizational standards. From the previous frameworks, they overlook the two parameters such as job training and transformational leadership where these parameters are giving significant impact to improve the organizational performance. This paper would like to enhance the present framework taking into consideration the two parameters mentioned earlier. The results shows that there is a strong relationship between transformational leadership and job training significantly improve employee performance.